From literature to film: an approach to a theory of adaptation - Gómez López, Encarnación (Revista de Filología Alemana, 2011)
Film versions of literature have been around for a long time. Numerous studies have put forward a theory of adaptation in an attempt to place film in a similar artistic category to literature, as for years film has been seen as a minor art compared to literature. Germany has produced important theorists and scholars on this topic, such as Sigfried Krakauer and Alfred Estermann; more recently Joachim Paech, Irmela Schneider and Franz-Josef Albersmeier and, in Spain, Mario Saalbach. In the early days, literary adaptation for film was studied using literary theory. Today, the trend is to look for a less literary theory, such as Intermedialität or Polysystem theory, in which a number of arts are mixed. To conclude, I propose studying adaptation using Reception theory, where the readers of a literary work relate what they have read to their personal experiences and how those readers change what is read to become the authors of new works in a different medium, that of film.